2022
DOI: 10.3390/toxins14120844
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin Therapy in the Clinical Management of Laryngeal Dystonia

Abstract: Laryngeal dystonia (LD), or spasmodic dysphonia (SD), is a chronic, task-specific, focal movement disorder affecting the larynx. It interferes primarily with the essential functions of phonation and speech. LD affects patients’ ability to communicate effectively and significantly diminishes their quality of life. Botulinum neurotoxin was first used as a therapeutic agent in the treatment of LD four decades ago and remains the standard of care for the treatment of LD. This article provides an overview of the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 139 publications
0
0
0
Order By: Relevance
“…The study also showed that early initiation of botulinum neurotoxin therapy is more beneficial than treatment in the advanced phase of pain. [37][38][39][40][41][42]…”
Section: Botulinum Neurotoxinmentioning
confidence: 99%
“…The study also showed that early initiation of botulinum neurotoxin therapy is more beneficial than treatment in the advanced phase of pain. [37][38][39][40][41][42]…”
Section: Botulinum Neurotoxinmentioning
confidence: 99%